Excision of staphylococcal cassette chromosome mec in methicillin-resistant Staphylococcus aureus assessed by quantitative PCR. (December 2015) - Stojanov, Miloš; Moreillon, P.; Sakwinska, O.
Abstract Background Methicillin-resistance in staphylococci is conferred by themecA gene, located on the genomic island Staphylococcal Cassette Chromosomemec (SCCmec ). SCCmec mobility relies on the Ccr recombinases, which catalyze insertion and excision form the host's chromosome. Although being a crucial step in its horizontal transfer, little is known about the dynamics of SCCmec excision. Results A quantitative PCR-based method was used to measure the rate of SCCmec excision by amplifying the chromosome–chromosome junction and the circularized SCCmec resulting from excision. SCCmec excision rate was measured in methicillin-resistantStaphylococcus aureus (MRSA) strain N315 at various growth times in broth cultures. In the present experimental settings, excision of SCCmec occurred at a rate of approximately 2 × 10−6 in MRSA N315. Conclusion This work brings new insights in the poorly understood SCCmec excision process. The results presented herein suggest a model in which excision occurs during a limited period of time at the early stages of growth.